Pengamatan Morphologi Oksidasi Mikrostruktur Lapisan Kerak Korosi Pada Paduan Ni-Al - Sahlan Sahlan (Faculty of Industrial Technology Universitas Islam Indonesia, 2008)
The impeller of air plane turbine or electrical generator gas turbine, generally used Ni base content superalloy. For long time turbine operation, oxidation of Ni-alloy could be happened. This research want to know the effect of the high temperature and time duration of turbine operation, especially oxidation of Ni-3Al alloy. In this research the temperature treatment at 1298 and 1498 oK, while time duration 20,25 and 50 hours. The research result shows that NiO Oxid is formed and porous crystall granulars are identified. This porous crystalls are Ni Al2O4. Keywords: Superalloy, Ni-Al, porous crystall, NiO.